Makkah is the ultimate multilingual phenomenon - Alhamami, Munassir (Penerbit Universiti Kebangsaan Malaysia, 2018)
The majority of the published studies on multilingualism concentrate on education, while only a few published papers describe this concept outside the education environment. The current descriptive study uses Makkah City as an example to describe two multilingual phenomena: Umrah and Hajj as examples of permanent and temporary multilingualism phenomena, respectively. This study uses government and published statistics to illustrate each multilingual phenomenon. First, this research describes temporary multilingual phenomenon and uses Hajj to illustrate it. Second, the current study describes permanent multilingualism phenomenon by using Umrah as an example. Third, this study discusses the issues related to the diversity of native speakers in one location. Lastly, research agendas are suggested.